Long‐acting recombinant factor IX Fc fusion protein (rFIXFc) for perioperative management of subjects with haemophilia B in the phase 3 B‐LONG study. (11th September 2014) - Powell, Jerry S.; Apte, Shashikant; Chambost, Hervé; Hermans, Cedric; Jackson, Shannon; Josephson, Neil C.; Mahlangu, Johnny N.; Ozelo, Margareth C.; Peerlinck, Kathelijne; Pasi, John; Perry, David; Ragni, Margaret V.; et al.
Summary In the phase 3 B‐LONG (Recombinant Factor IX Fc Fusion Protein [rFIXFc] in Subjects With Haemophilia B) study, rFIXFc demonstrated a prolonged half‐life compared with recombinant factor IX (rFIX), and safety and efficacy for prophylaxis and treatment of bleeding in subjects with moderately‐severe to severe haemophilia B. In this B‐LONG sub‐analysis, rFIXFc was evaluated for efficacy in subjects requiring major surgery. Dosing was investigator‐determined. Assessments included dosing, consumption, bleeding, transfusions and haemostatic response. A population pharmacokinetics model of rFIXFc was used to predict FIX activity. Twelve subjects underwent 14 major surgeries (including 11 orthopaedic surgeries); most subjects (11/12) received rFIXFc prophylaxis before surgery (range, ~2 weeks–12 months). Investigators/surgeons rated haemostatic responses as excellent (n = 13) or good (n = 1). In most surgeries (85·7%), haemostasis from the pre‐surgical dose until the end of surgery was maintained with a single rFIXFc infusion. Blood loss was consistent with similar surgeries in subjects without haemophilia. The strong correlation (R2 = 0·9586, P < 0·001) between observed and population pharmacokinetic model‐predicted FIX activity suggests surgery did not impact rFIXFc pharmacokinetics. No unique safety concerns or inhibitors were observed. In conclusion, rFIXFc was safe and efficacious, with prolonged dosing intervals and low consumption, when used perioperatively in haemophilia B. Surgery did not appear to alter rFIXFc pharmacokinetics.